2015
DOI: 10.5935/0103-5053.20150335
|View full text |Cite
|
Sign up to set email alerts
|

Application of Enzymes in Sunflower Oil Extraction: Antioxidant Capacity and Lipophilic Bioactive Composition

Abstract: A 2 3 factorial design with center point in triplicate was used to evaluate the application of different enzymes in extraction of sunflower oil, comparing its quality with the oil obtained by conventional methods (solvent and pressing) in relation to antioxidant capacity, phytosterol and tocopherol contents, and fatty acid composition. Three enzymes were used; Pectinex Ultra SPL, Celluclast 1.5 L and Alcalase 2.4 L; and three factors were evaluated: enzyme concentration, sample/water ratio and extraction time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…The oil content of the sunflower seeds, determined in a Soxhlet extractor with n ‐hexane as the solvent, was 57.23% ± 0.06. Latif and Anwar () and Ribeiro et al () reported oil values of 45.5 and 55.1%, respectively, in sunflower seeds extracted with n ‐hexane. Differences in the oil content of sunflower seeds are related to the regions in which the oilseeds were cultivated, because factors like the soil and climate affect the composition of the sunflower seeds (Castro & Leite, ).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The oil content of the sunflower seeds, determined in a Soxhlet extractor with n ‐hexane as the solvent, was 57.23% ± 0.06. Latif and Anwar () and Ribeiro et al () reported oil values of 45.5 and 55.1%, respectively, in sunflower seeds extracted with n ‐hexane. Differences in the oil content of sunflower seeds are related to the regions in which the oilseeds were cultivated, because factors like the soil and climate affect the composition of the sunflower seeds (Castro & Leite, ).…”
Section: Resultsmentioning
confidence: 98%
“…Abdulkarim, Lai, Muhammad, Long, and Ghazali () verified the influence of temperature in the range of 45–60°C on the EAE of Moringa oleifera oil with the enzyme Celluclast 1.5 L and observed that the highest yield was obtained at 60°C. Sineiro et al () and Ribeiro et al () used Celluclast 1.5 L in the EAE of sunflower oil at 50°C, but the influence of temperature on the oil yield was not evaluated. Although the optimal temperature range of the enzyme Celluclast 1.5L is 50–60°C, most studies with this enzyme are conducted at 50°C.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations